The burden of the past : - Kimura, Kan (Japan Publishing Industry Foundation for Culture, 2019)
The Burden of the Past reexamines the dispute over historical perception between Japan and South Korea, going beyond the descriptive emphasis of previous studies to clearly identify the many independent variables that have affected the situation. From the history textbook debates, to the Occupation-period exploitation of “comfort women,” to the Dokdo/Takeshima territory dispute and Yasukuni Shrine visits, Professor Kimura traces the rise and fall of popular, political, and international concerns underlying these complex and highly fraught issues.